2012
DOI: 10.1590/s0102-33062012000100007
|View full text |Cite
|
Sign up to set email alerts
|

When hummingbirds are the thieves: visitation effect on the reproduction of Neotropical snowbell Styrax ferrugineus Nees & Mart (Styracaceae)

Abstract: The spectrum of floral visitors associated with a particular plant is frequently larger than predicted by the traditional concept of floral syndromes and the role that unpredicted visitors play in plant reproduction deserves attention. Hummingbirds are frequently recorded visiting flowers with distinct floral syndromes, especially in some hummingbird flower poor ecosystem such as the Cerrado. In this study we investigated the effect of frequent hummingbird visits on the reproduction of melittophilous Styrax fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…The small amount of accumulated nectar in species with a great amount of flowers can force floral visitors to shorten their visits and to visit a greater number of flowers in order to collect the number of calories needed. Studies involving hummingbirds suggest that plants presenting flowers with little or no nectar may save energy and promote pollinator movement, in mimicry of flowers with uniform secretion rates, but with variable nectar availability due to foraging activity (Feinsinger 1978;Maruyama et al 2012). In addition, one experimental study showed that when the number of "empty" (nectarless) flowers increases in an inflorescence, the number of visits by bees decreases (Ishii et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small amount of accumulated nectar in species with a great amount of flowers can force floral visitors to shorten their visits and to visit a greater number of flowers in order to collect the number of calories needed. Studies involving hummingbirds suggest that plants presenting flowers with little or no nectar may save energy and promote pollinator movement, in mimicry of flowers with uniform secretion rates, but with variable nectar availability due to foraging activity (Feinsinger 1978;Maruyama et al 2012). In addition, one experimental study showed that when the number of "empty" (nectarless) flowers increases in an inflorescence, the number of visits by bees decreases (Ishii et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Given the positive correlation between the percentage of empty flowers and the number of flowers per inflorescence (Takar et al 2003), larger displays promote proportionally fewer effective visits by bees (Ishii et al 2008). Therefore, the benefits of large displays in selfincompatible plants may be increased by the presence of empty flowers, encouraging cross-pollinations, although geitonogamy is also favored until pollinators leave one tree to visit another (Maruyama et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Tampouco foram agrupadas as plantas polinizadas por abelhas pequenas entre aquelas polinizadas por insetos pequenos ou muito pequenos (e.g., Oliveira & Gibbs 2000), uma vez que abelhas grandes, como espécies de Xylocopa podem visitar e polinizar efetivamente plantas com flores pequenas (Silva et al 2010) e abelhas pequenas também visitam flores grandes e/ou com corola tubular longa, agindo inclusive como polinizadores efetivos . Como no caso de polinização por beija-flores (Maruyama et al 2012), as abelhas usaram uma espectro grande de recursos florais. Mesmo quando não são importantes para a polinização das plantas visitadas, os recursos oferecidos por estas plantas podem ser vitais para a persistência das populações de abelhas na ausência de outras fontes de alimentos.…”
Section: Discussionunclassified
“…In this regard, the direct contribution of hummingbirds to plant reproduction may be low, even when they are the most frequent visitors (Maruyama et al . , Watts et al . ).…”
Section: Discussionmentioning
confidence: 99%